9-Vinyl-9H-carbazole-3,6-dicarbonitrile - Kristina Svetlova; Alexander Kazantsev; Oleg Levin; Sofia Filippova; Elena Alekseeva (Molbank, 2024)
Carbazole polymers attract significant attention as promising luminophores, organic electronic and photovoltaic materials, photo/electrocatalysts, energy storage materials, redox mediators and catalysts. However, the oxidation potential of the commercially available poly(vinylcarbazole) is insufficient for some applications such as high-voltage Li-Ion batteries. We have proposed a monomer for the novel polycarbazole with an increased oxidation potential, which will be compatible with high-voltage cathode materials for Li-Ion. In addition, the proposed polymer is an interesting substrate for the further carbonization to obtain N-doped carbons with a high electrocatalytic activity level.